Silicon-carbon composite material as well as preparation method and application thereof

By neutralizing the outer surface of the silica aerogel and loading carbon source material on the pores, the silicon-carbon composite material with a pore structure was prepared through step-by-step temperature-raising curing, carbonization treatment and activation reaction, which solved the problems of high expansion rate, poor circulation and high manufacturing cost of silicon-carbon materials, and achieved efficient and economical preparation technology and excellent electrochemical properties.

CN119890211APending Publication Date: 2025-04-25LIYANG TIANMU PILOT BATTERY MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311394718.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-25
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing silicon-carbon materials have high expansion rate, poor circulation and high manufacturing costs during circulation.

Method used

Silicon-carbon composite material with pore structure was prepared by neutralizing the outer surface of the silica aerogel and sequentially through step-by-step temperature-raising curing, carbonization treatment and activation reactions.

Benefits of technology

This method simplifies the preparation process, reduces costs, improves the cycle stability and specific capacity of silicon-carbon composite materials, and simultaneously inhibits the occurrence of volume expansion and side reactions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890211A_ABST
    Figure CN119890211A_ABST
Patent Text Reader

Abstract

The invention discloses a silicon-carbon composite material as well as a preparation method and application thereof, and the preparation method comprises the following steps: uniformly mixing a carbon source material, polyvinylpyrrolidone and alcohol in a stirring tank to obtain a first mixed solution; placing the first mixed solution in a sand mill, adding silicon dioxide aerogel, and sanding to obtain a second mixed solution; drying the second mixed solution to obtain a silicon-carbon precursor; uniformly dispersing the silicon-carbon precursor in a sagger, placing the sagger in a box-type furnace, and carrying out stepped heating curing to obtain a solid compound; placing the solid compound in a rotary furnace, performing carbonization treatment in an inert gas environment, grinding, crushing and sieving to obtain a carbonized compound; and performing an activation reaction on the carbonized compound in a carbon dioxide atmosphere to obtain the silicon-carbon composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a silicon-carbon composite material and a preparation method and application thereof. Background Art

[0002] Silicon (Si) is considered as a candidate material for the negative electrode of the next generation of lithium-ion batteries (LIB) because of its high theoretical specific capacity (4200mAh / g), low lithium insertion potential, fast reaction kinetics and abundant reserves. The current synthesis route for preparing silicon-carbon materials mainly uses special synthesis processes, such as chemical vapor deposition, liquid phase impregnation, hydrothermal self-assembly, etc. However, the commercialization of silicon-carbon negative electrodes has been slow, mainly due to the failure of the electrode during the cycle, including mechanical failure and electrochemical failure. Both of these failure modes are derived from the huge volume expansion of silicon materials. In order to reduce the expansion rate of the pole piece, the current existing methods include: reducing the particle size to prepare nano-silicon; constructing core-shell structures and silicon material coatings. However, the preparation of nano-silicon, core-shell structures and silicon material coatings is difficult and costly. Therefore, developing a simple and efficient preparation process will be more conducive to new silicon-carbon materials to meet the needs of special applications. Summary of the invention

[0003] The purpose of the present invention is to provide a silicon-carbon composite material and a preparation method and application thereof, so as to solve the problems of high expansion rate, poor cyclability and high manufacturing cost of existing traditional silicon-carbon materials.

[0004] To this end, in a first aspect, an embodiment of the present invention provides a method for preparing a silicon-carbon composite material, the preparation method comprising:

[0005] Step S1, placing the carbon source material, polyvinyl pyrrolidone and alcohol in a stirring tank and mixing them evenly to obtain a first mixed solution;

[0006] Step S2, placing the first mixed solution in a sand mill, adding the silica aerogel, and performing sand milling to make the carbon source material evenly distributed in the pores of the silica aerogel, thereby obtaining a second mixed solution;

[0007] Step S3, drying the second mixed solution to obtain a silicon-carbon precursor;

[0008] Step S4, uniformly dispersing the silicon-carbon precursor in a box pot, placing the box pot in a box furnace, and performing stepwise temperature rise curing to obtain a solid composite;

[0009] Step S5, placing the solid composite in a rotary kiln, performing carbonization treatment under an inert gas environment, grinding, crushing and screening to obtain a carbonized composite;

[0010] Step S6, switching the gas introduced into the rotary kiln to carbon dioxide gas to exclude inert gas, activating the carbonized composite in a carbon dioxide atmosphere, and then switching the gas introduced into the rotary kiln to inert gas, and naturally cooling in an inert gas environment to obtain a silicon-carbon composite material.

[0011] Preferably, the carbon source material is a thermosetting alcohol-soluble resin, specifically including: one or more of phenolic resin, epoxy resin, melamine resin, and acrylic resin;

[0012] The particle size Dv50 of the silica aerogel is 1 μm-5 mm; the pore size of the silica aerogel is 1 nm-100 nm, and the porosity is 80%-90%.

[0013] The concentration of the alcohol is greater than or equal to 99%;

[0014] The mass ratio of the carbon source material, polyvinyl pyrrolidone and alcohol is [1-6]: [1-3]: [10-30];

[0015] The mass ratio of the carbon source material to the silica aerogel is [100-1000]:[1-5].

[0016] Preferably, the rotation speed of the sand mill is 1200 rpm-4000 rpm, and the sand milling time is 1 hour-3 hours.

[0017] Preferably, the drying method includes closed spray drying, and the equipment used is a closed cycle spray dryer; the specific conditions of the closed spray drying are: setting the air inlet temperature to 150°C-200°C, the air outlet temperature to 80°C-150°C, and the frequency of the atomizer to 220Hz-280Hz;

[0018] The mesh size of the solid composite after grinding, pulverizing and screening is in the range of 80 meshes to 300 meshes.

[0019] Preferably, the program setting of the step-by-step temperature curing is specifically as follows: heating to 70°C-100°C at a heating rate of 1°C / min-5°C / min, keeping warm for 10 hours-24 hours, then heating to 150°C-250°C at a heating rate of 1°C / min-3°C / min, keeping warm for 6 hours-12 hours, and then naturally cooling to room temperature.

[0020] Preferably, the inert gas includes nitrogen and / or argon; the flow rate of the inert gas is 0.5L / min-3L / min;

[0021] The carbonization treatment program is specifically set as follows: heating to 400°C-700°C at a heating rate of 3°C / min-5°C / min, keeping the temperature for 2 hours-8 hours, and naturally cooling to room temperature;

[0022] The specific process of causing the carbonized composite to undergo an activation reaction under a carbon dioxide atmosphere is as follows: switching the inert gas to carbon dioxide gas, using carbon dioxide gas as the activation atmosphere, with a carbon dioxide gas flow rate ranging from 2L / min to 8L / min, then heating to 800°C to 1400°C at a heating rate of 1°C / min to 3°C / min, keeping the temperature for 6 hours to 18 hours, then switching the carbon dioxide gas to an inert gas, and naturally cooling to room temperature.

[0023] In a second aspect, an embodiment of the present invention provides a silicon-carbon composite material prepared by the preparation method described in the first aspect, wherein the silicon-carbon composite material comprises: a silicon dioxide matrix containing pores, silicon particles and carbon particles distributed in the pores of the silicon dioxide matrix, and a silicon layer and a carbon coating layer sequentially coated on the outer surface of the silicon dioxide matrix;

[0024] The silicon-carbon composite material is obtained by loading carbon source materials in the pores and on the outer surface of the silicon dioxide aerogel and sequentially undergoing step-by-step temperature curing, carbonization treatment, and activation reaction.

[0025] Preferably, the average particle size of the silica matrix is ​​between 1 μm and 10 μm; the pore size of the silica matrix is ​​between 1 nm and 100 nm; the average particle size of the silicon particles is between 1 nm and 100 nm;

[0026] The mass of the carbon coating layer accounts for 0.5%-10% of the total mass of the silicon-carbon composite material;

[0027] The mass of the silicon particles accounts for 5% to 35% of the total mass of the silicon-carbon composite material;

[0028] The thickness of the silicon layer is 1 nm-7 μm; the thickness of the carbon coating layer is 10 nm-30 μm.

[0029] In a third aspect, an embodiment of the present invention provides a negative electrode plate, wherein the negative electrode plate comprises the silicon-carbon composite material described in the second aspect.

[0030] In a fourth aspect, an embodiment of the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the negative electrode sheet described in the third aspect.

[0031] The embodiment of the present invention provides a silicon-carbon composite material and a preparation method and application thereof. The silicon-carbon composite material is obtained by loading a carbon source material in the pores and on the outer surface of a silicon dioxide aerogel, and sequentially undergoing step-by-step temperature curing, carbonization treatment, and activation reaction. The present invention uses silicon dioxide aerogel as a raw material, which has the advantages of high porosity, low density, high specific surface area, controllable structure, and good stability, so that the silicon-carbon composite material has a special structure. The silicon dioxide matrix of the silicon-carbon composite material has a pore structure, silicon particles are distributed in the pores, and the outer surface of the silicon dioxide matrix has a silicon layer and a carbon coating layer. On the one hand, the silicon particles can increase the specific capacity of the silicon-carbon composite material, and on the other hand, the pore structure in the silicon dioxide matrix can inhibit the volume expansion of the silicon particles, and the carbon coating layer can inhibit the occurrence of side reactions of the silicon-carbon material. The silicon-carbon composite material is used as a negative electrode active material in a lithium ion battery to improve the cycle stability of the lithium ion battery.

[0032] The preparation method provided by the embodiment of the present invention has the advantages of simple preparation process, controllable operating conditions, low raw material price, high purity of the prepared silicon-carbon composite material, and easy industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The technical solution of the embodiment of the present invention is further described in detail below through the drawings and examples.

[0034] Figure 1 It is a flow chart of a method for preparing a silicon-carbon composite material provided in an embodiment of the present invention.

[0035] Figure 2 It is a schematic diagram of the structure of the silicon-carbon composite material provided in an embodiment of the present invention.

[0036] Figure 3 This is a scanning electron microscope (SEM) image of the silicon-carbon composite material provided in Example 1 of the present invention. DETAILED DESCRIPTION

[0037] The present invention is further described in detail below through the accompanying drawings and specific embodiments, but it should be understood that these embodiments are only used for more detailed description and should not be understood as limiting the present invention in any form, that is, they are not intended to limit the protection scope of the present invention.

[0038] The present invention provides a method for preparing a silicon-carbon composite material. Figure 1 As shown, the carbon source material is loaded in the pores and on the outer surface of the silica aerogel and sequentially subjected to step-wise temperature curing, carbonization treatment, and activation reaction, which specifically includes the following steps:

[0039] Step S1, placing the carbon source material, polyvinyl pyrrolidone and alcohol in a stirring tank and mixing them evenly to obtain a first mixed solution;

[0040] The carbon source material is a thermosetting alcohol-soluble resin, specifically including one or more of phenolic resin, epoxy resin, melamine resin, and acrylic resin;

[0041] The silica aerogel used in the present invention is a conventional commercial material, and the particle size range Dv50 of the silica aerogel is 1 μm-5 mm, preferably 100 μm-5 mm; the pore size of the silica aerogel is 1 nm-100 nm, preferably 20 nm-100 nm, and the porosity is 80%-90%;

[0042] The alcohol concentration is greater than or equal to 99%;

[0043] The mass ratio of carbon source material, polyvinyl pyrrolidone (PVP) and alcohol is [1-6]: [1-3]: [10-30];

[0044] The mass ratio of the carbon source material to the silica aerogel is [100-1000]:[1-5].

[0045] Step S2, placing the first mixed solution in a sand mill, adding the silica aerogel, and performing sand milling to make the carbon source material evenly distributed in the pores of the silica aerogel, thereby obtaining a second mixed solution;

[0046] The rotation speed of the sand mill is 1200 rpm-4000 rpm, and the sand milling time is 1 hour-3 hours. The present invention adopts the sand milling method to better evenly disperse the silica aerogel in the first mixed solution.

[0047] Step S3, drying the second mixed solution to obtain a silicon-carbon precursor;

[0048] Among them, the drying method includes closed spray drying, and the equipment used is a closed-cycle spray dryer; the specific conditions of closed spray drying are: setting the air inlet temperature to 150℃-200℃, the air outlet temperature to 80℃-150℃, and the atomizer frequency to 220Hz-280Hz.

[0049] Step S4, uniformly dispersing the silicon-carbon precursor in a box pot, placing the box pot in a box furnace, and performing stepwise temperature rise curing to obtain a solid composite;

[0050] The program setting of the step-by-step temperature curing is as follows: heating to 70-100°C at a heating rate of 1°C / min-5°C / min, keeping warm for 10-24 hours, then heating to 150-250°C at a heating rate of 1°C / min-3°C / min, keeping warm for 6-12 hours, and then naturally cooling to room temperature;

[0051] The present invention adopts step-by-step temperature curing to better cure the thermosetting alcohol-soluble resin in the silicon-carbon precursor. On the one hand, the morphology of the silicon-carbon precursor obtained by spray drying can be maintained to be spherical, so that it has a higher specific surface area, increases the contact area in the subsequent activation reaction process, increases the active sites, and is conducive to the activation reaction. On the other hand, the silicon-carbon precursor is prevented from volume expansion due to heat during the subsequent carbonization and activation process. The volume expansion will block the air inlet and outlet of the rotary kiln, resulting in the reaction being unable to proceed normally.

[0052] Step S5, placing the solid composite in a rotary kiln, performing carbonization treatment under an inert gas environment, grinding, crushing and screening to obtain a carbonized composite;

[0053] Wherein, the inert gas includes nitrogen and / or argon; the flow rate of the inert gas is 0.5L / min-3L / min;

[0054] The carbonization treatment program setting is as follows: heating to 400°C-700°C at a heating rate of 3°C / min-5°C / min, keeping the temperature for 2 hours-8 hours, and cooling naturally to room temperature;

[0055] The mesh size range of the solid composite grinding, crushing and screening is between 80 mesh and 300 mesh;

[0056] The carbonization process of the present invention is to carbonize the carbon source material in the pores and on the surface of the silica aerogel, that is, the thermosetting alcohol-soluble resin, into a single carbon substance; the mass of the single carbon substance obtained after carbonization accounts for about 50% of the mass of the carbon source material.

[0057] Step S6, switching the gas introduced into the rotary kiln to carbon dioxide gas to exclude inert gas, performing an activation reaction on the carbonized composite in a carbon dioxide atmosphere, and then switching the gas introduced into the rotary kiln to inert gas again, and naturally cooling in an inert gas environment to obtain a silicon-carbon composite material;

[0058] The specific process of making the carbonized composite undergo an activation reaction under a carbon dioxide atmosphere is as follows: switching the inert gas to carbon dioxide gas, using carbon dioxide gas as the activation atmosphere, with a carbon dioxide gas flow rate ranging from 2L / min to 8L / min, then heating to 800°C to 1400°C at a heating rate of 1°C / min to 3°C / min, keeping the temperature for 6 hours to 18 hours, then switching the carbon dioxide gas to an inert gas, and naturally cooling to room temperature;

[0059] The activation reaction process of the present invention includes a process in which the silicon dioxide aerogel reacts with the carbon single substance in the carbonized composite obtained in step S5 to generate silicon particles, and the reaction equation is SiO2+2C=Si+2CO↑; in addition, it also includes a process in which the introduced carbon dioxide gas reacts with part of the carbon single substance in the carbonized composite obtained in step S5 at a high temperature to generate carbon monoxide gas for discharge, and pores are formed at the positions of the reacted carbon single substance particles, so that the matrix of the silicon-carbon composite material has pores inside to inhibit the expansion of the silicon particles.

[0060] After the activation reaction, the content of the carbon element in the material accounts for about 10%-15% of the mass of the carbon source material.

[0061] The silicon-carbon composite material prepared by the above preparation method in the embodiment of the present invention includes: a silica matrix containing pores, silicon particles and carbon particles distributed in the pores of the silica matrix, and a silicon layer and a carbon coating layer sequentially coated on the outer surface of the silica matrix.

[0062] Among them, the carbon coating layer is obtained by pre-coating the carbon source material on the surface of the silica aerogel and then undergoing carbonization treatment; the silicon layer is a tightly arranged silicon particle layer formed by the activation reaction of the carbon in the carbon coating layer obtained after the carbonization treatment on the surface of the silica aerogel particles; the average particle size of the silica matrix is ​​between 1μm-10μm, and the pore size of the silica matrix is ​​between 1nm-100nm; the average particle size of the silicon particles and the carbon particles is between 1nm-100nm; the thickness of the silicon layer is between 1nm-7μm; the thickness of the carbon coating layer is between 10nm-30μm.

[0063] The mass of the carbon coating layer accounts for 0.5%-10% of the total mass of the silicon-carbon composite material; the mass of the silicon particles accounts for 5%-35% of the total mass of the silicon-carbon composite material.

[0064] The schematic diagram of the structure of the silicon-carbon composite material of the present invention is as follows: Figure 2 As shown, it can be seen that the silicon-carbon composite material includes a silicon dioxide matrix containing pores, and a silicon layer and a carbon coating layer coated on the outer surface of the silicon dioxide matrix, wherein silicon particles and carbon particles are distributed in the pores of the silicon dioxide matrix.

[0065] The silicon-carbon composite material provided in the embodiment of the present invention can be used to prepare a negative electrode plate. Applying the negative electrode plate containing the silicon-carbon composite material to a lithium-ion battery can effectively improve the first-cycle coulombic efficiency and cycle stability of the lithium-ion battery.

[0066] In order to better understand the technical solution provided by the present invention, the preparation process and characteristics of the silicon-carbon composite material of the present invention are respectively described below with multiple specific examples.

[0067] Example 1

[0068] This embodiment provides a preparation process and performance test of a silicon-carbon composite material, and the specific process is as follows:

[0069] (1) 2 kg of phenolic resin is used as a carbon source material, and the carbon source material, polyvinyl pyrrolidone and alcohol are taken in a stirring tank in a mass ratio of 2:1:12 and mixed evenly to obtain a first mixed solution.

[0070] (2) The first mixed solution was placed in a sand mill, 20 g of silica aerogel was added, and the mixture was sand milled at a speed of 1200 rpm for 2 hours to make the phenolic resin evenly distributed in the pores of the silica aerogel, thereby obtaining a second mixed solution.

[0071] (3) The second mixed solution is spray-dried in a closed manner with an air inlet temperature of 165° C., an air outlet temperature of 85° C., and an atomizer frequency of 220 Hz to obtain a silicon-carbon precursor.

[0072] (4) The silicon-carbon precursor is evenly dispersed in a box pot, placed in a box furnace, and heated to 90°C at a rate of 3°C / min, kept warm for 12 hours, then heated to 150°C at a rate of 3°C / min, kept warm for 6 hours, and naturally cooled to room temperature. After step-wise heating and curing, a solid composite is obtained.

[0073] (5) The solid composite was placed in a rotary kiln for carbonization treatment. The temperature was raised to 600° C. at a rate of 3° C. / min in a nitrogen atmosphere with a gas flow rate of 2 L / min, and the temperature was kept at that temperature for 3 hours. The temperature was naturally cooled to room temperature, and the solid composite was ground and sieved (200 mesh) to obtain a carbonized composite.

[0074] (6) The gas introduced into the rotary kiln is switched to carbon dioxide gas to exclude nitrogen gas. The gas flow rate of carbon dioxide gas is 4 L / min. The temperature of the rotary kiln is increased to 1050°C at a rate of 3°C / min to activate the carbonized composite in a carbon dioxide atmosphere. Subsequently, the gas introduced into the rotary kiln is switched to nitrogen gas, and the mixture is naturally cooled in a nitrogen gas environment to finally obtain a silicon-carbon composite material.

[0075] The SEM image of the laser-cut section of the silicon-carbon composite material prepared in this embodiment is as follows: Figure 3 As shown, the thickness of the carbon coating layer is measured to be between 10nm-30nm, and the thickness of the silicon layer is between 1nm-7nm. In the SEM image, it can be seen that the substances in the middle part are silicon particles, silicon dioxide matrix and carbon particles, as well as pore structure.

[0076] The silicon-carbon composite material prepared in this embodiment was used to prepare a negative electrode plate and assembled into a CR2032 button battery for testing. The specific process is as follows.

[0077] Preparation of negative electrode sheets: Graphite, silicon-carbon composite material, carbon black and binder polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 65:31:1:3 and dispersed in deionized water to form a uniform slurry; the slurry is then cast on a copper foil by a doctor blade method, and after baking at 80°C for 4 hours, it is cold pressed, trimmed and cut into pieces, and then dried at 95°C under vacuum conditions for 16 hours to obtain a negative electrode sheet.

[0078] Assemble CR2032 button cells: in a glove box filled with inert gas (wherein the contents of H2O and O2 are both less than 0.1ppm), use metal lithium sheets as counter electrodes, PP / PE as separators, and 1 mol / L LiPF6 solution as electrolyte, wherein the solvent in the electrolyte is a mixed solution of 97wt% ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) (wherein the volume ratio of EC, EMC, and DMC is 1:1:1) + 3wt% fluoroethylene carbonate (FEC).

[0079] Electrochemical performance test:

[0080] (1) Cyclic performance test

[0081] Take 3 batteries from each group assembled in the present embodiment, and repeatedly charge and discharge the batteries through the following steps, and calculate the discharge capacity retention rate of the batteries.

[0082] First, in an environment of 25°C, charge to 1.5V at 0.1C current density, then discharge to 5mV at 0.5C current density, discharge to 5mV at 0.05C density, discharge to 5mV at 0.02C current density, discharge to 5mV at 0.01C density, and record the charge capacity of the first cycle. Then perform 300 cycles of discharge and charge cycles, with a charge rate of 0.5C and a discharge rate of 1C during the cycle, and record the charge capacity of the 300th cycle.

[0083] The cycle capacity retention rate was calculated according to the following formula: cycle capacity retention rate = first cycle specific capacity / 300th cycle specific capacity × 100%.

[0084] The average capacity retention rates of the three groups of batteries after 300 cycles are calculated, as shown in Table 1.

[0085] (2) Thickness expansion rate test of negative electrode fully embedded state

[0086] The thickness of the negative electrode sheet before assembling the battery was measured, recorded as D1. The assembled battery was discharged to 5mV at 0.1C and then to 5mV at 0.02C in a 25°C environment, so that the negative electrode sheet was in a fully embedded state. The battery was disassembled and the thickness of the negative electrode sheet in the fully embedded state was measured, recorded as D2. The thickness of the foil used was 9μm. The thickness expansion rate was calculated according to the following formula: thickness expansion rate = (D2-D1) / (D1-9)×100%. The test data is shown in Table 1.

[0087] Example 2

[0088] This embodiment provides a preparation process and performance test of a silicon-carbon composite material, and the specific process is as follows:

[0089] (1) 2 kg of phenolic resin is used as a carbon source material, and the carbon source material, polyvinyl pyrrolidone and alcohol are taken in a stirring tank in a mass ratio of 2:1:12 and mixed evenly to obtain a first mixed solution.

[0090] (2) The first mixed solution was placed in a sand mill, 10 g of silica aerogel was added, and the mixture was sand milled at a speed of 1200 rpm for 2 hours to make the phenolic resin evenly distributed in the pores of the silica aerogel, thereby obtaining a second mixed solution.

[0091] (3) The second mixed solution is spray-dried in a closed manner with an air inlet temperature of 165° C., an air outlet temperature of 85° C., and an atomizer frequency of 220 Hz to obtain a silicon-carbon precursor.

[0092] (4) The silicon-carbon precursor is evenly dispersed in a box pot, placed in a box furnace, and heated to 90°C at a rate of 3°C / min, kept warm for 12 hours, then heated to 150°C at a rate of 3°C / min, kept warm for 6 hours, and naturally cooled to room temperature. After step-wise heating and curing, a solid composite is obtained.

[0093] (5) The solid composite was placed in a rotary kiln for carbonization treatment. The temperature was raised to 600° C. at a rate of 3° C. / min in a nitrogen atmosphere with a gas flow rate of 2 L / min, and the temperature was kept at that temperature for 3 hours. The temperature was naturally cooled to room temperature, and the solid composite was ground and sieved (200 mesh) to obtain a carbonized composite.

[0094] (6) The gas introduced into the rotary kiln is switched to carbon dioxide gas to exclude nitrogen gas. The gas flow rate of carbon dioxide gas is 4 L / min. The temperature of the rotary kiln is increased to 1050°C at a rate of 3°C / min to activate the carbonized composite in a carbon dioxide atmosphere. Subsequently, the gas introduced into the rotary kiln is switched to nitrogen gas, and the mixture is naturally cooled in a nitrogen gas environment to finally obtain a silicon-carbon composite material.

[0095] The silicon-carbon composite material prepared in this embodiment was used to prepare the negative electrode plate and assembled into a CR2032 button battery for testing. The specific process was the same as that in Example 1. The test data is detailed in Table 1.

[0096] Example 3

[0097] This embodiment provides a preparation process and performance test of a silicon-carbon composite material, and the specific process is as follows:

[0098] (1) 4 kg of epoxy resin is used as a carbon source material, and the carbon source material, polyvinyl pyrrolidone and alcohol are taken in a stirring tank in a mass ratio of 3:1:12, and mixed evenly to obtain a first mixed solution.

[0099] (2) The first mixed solution was placed in a sand mill, 15 g of silica aerogel was added, and the mixture was sand milled at a speed of 1200 rpm for 2 hours to make the phenolic resin evenly distributed in the pores of the silica aerogel, thereby obtaining a second mixed solution.

[0100] (3) The second mixed solution is spray-dried in a closed manner with an air inlet temperature of 165° C., an air outlet temperature of 85° C., and an atomizer frequency of 220 Hz to obtain a silicon-carbon precursor.

[0101] (4) The silicon-carbon precursor is evenly dispersed in a box pot, placed in a box furnace, and heated to 90°C at a rate of 3°C / min, kept warm for 12 hours, then heated to 150°C at a rate of 3°C / min, kept warm for 6 hours, and naturally cooled to room temperature. After step-wise heating and curing, a solid composite is obtained.

[0102] (5) The solid composite was placed in a rotary kiln for carbonization treatment. The temperature was raised to 600° C. at a rate of 3° C. / min in a nitrogen atmosphere with a gas flow rate of 2 L / min, and the temperature was kept at that temperature for 3 hours. The temperature was naturally cooled to room temperature, and the solid composite was ground and sieved (200 mesh) to obtain a carbonized composite.

[0103] (6) The gas introduced into the rotary kiln is switched to carbon dioxide gas to exclude nitrogen gas. The gas flow rate of carbon dioxide gas is 4 L / min. The temperature of the rotary kiln is increased to 1050°C at a rate of 3°C / min to activate the carbonized composite in a carbon dioxide atmosphere. Subsequently, the gas introduced into the rotary kiln is switched to nitrogen gas, and the mixture is naturally cooled in a nitrogen gas environment to finally obtain a silicon-carbon composite material.

[0104] The silicon-carbon composite material prepared in this embodiment was used to prepare the negative electrode plate and assembled into a CR2032 button battery for testing. The specific process was the same as that in Example 1. The test data is detailed in Table 1.

[0105] Example 4

[0106] This embodiment provides a preparation process and performance test of a silicon-carbon composite material, and the specific process is as follows:

[0107] (1) 5 kg of melamine resin was used as a carbon source material, and the carbon source material, polyvinyl pyrrolidone and alcohol were taken in a stirring tank in a mass ratio of 2:1:14 and mixed evenly to obtain a first mixed solution.

[0108] (2) The first mixed solution was placed in a sand mill, 25 g of silica aerogel was added, and the mixture was sand milled at a speed of 1200 rpm for 2 hours to make the phenolic resin evenly distributed in the pores of the silica aerogel, thereby obtaining a second mixed solution.

[0109] (3) The second mixed solution is spray-dried in a closed manner with an air inlet temperature of 165° C., an air outlet temperature of 85° C., and an atomizer frequency of 220 Hz to obtain a silicon-carbon precursor.

[0110] (4) The silicon-carbon precursor is evenly dispersed in a box pot, placed in a box furnace, and heated to 90°C at a rate of 3°C / min, kept warm for 12 hours, then heated to 150°C at a rate of 3°C / min, kept warm for 6 hours, and naturally cooled to room temperature. After step-wise heating and curing, a solid composite is obtained.

[0111] (5) The solid composite was placed in a rotary kiln for carbonization treatment. The temperature was raised to 600° C. at a rate of 3° C. / min in a nitrogen atmosphere with a gas flow rate of 2 L / min, and the temperature was kept at that temperature for 3 hours. The temperature was naturally cooled to room temperature, and the solid composite was ground and sieved (200 mesh) to obtain a carbonized composite.

[0112] (6) The gas introduced into the rotary kiln is switched to carbon dioxide gas to exclude nitrogen gas. The gas flow rate of carbon dioxide gas is 4 L / min. The temperature of the rotary kiln is increased to 1050°C at a rate of 3°C / min to activate the carbonized composite in a carbon dioxide atmosphere. Subsequently, the gas introduced into the rotary kiln is switched to nitrogen gas, and the mixture is naturally cooled in a nitrogen gas environment to finally obtain a silicon-carbon composite material.

[0113] The silicon-carbon composite material prepared in this embodiment was used to prepare the negative electrode plate and assembled into a CR2032 button battery for testing. The specific process was the same as that in Example 1. The test data is detailed in Table 1.

[0114] Example 5

[0115] This embodiment provides a preparation process and performance test of a silicon-carbon composite material, and the specific process is as follows:

[0116] (1) 5 kg of acrylic resin is used as a carbon source material, and the carbon source material, polyvinyl pyrrolidone and alcohol are taken in a stirring tank in a mass ratio of 2:1:14 and mixed evenly to obtain a first mixed solution.

[0117] (2) The first mixed solution was placed in a sand mill, 10 g of silica aerogel was added, and the mixture was sand milled at a speed of 1200 rpm for 2 hours to make the phenolic resin evenly distributed in the pores of the silica aerogel, thereby obtaining a second mixed solution.

[0118] (3) The second mixed solution is spray-dried in a closed manner with an air inlet temperature of 165° C., an air outlet temperature of 85° C., and an atomizer frequency of 220 Hz to obtain a silicon-carbon precursor.

[0119] (4) The silicon-carbon precursor is evenly dispersed in a box pot, placed in a box furnace, and heated to 90°C at a rate of 3°C / min, kept warm for 12 hours, then heated to 150°C at a rate of 3°C / min, kept warm for 6 hours, and naturally cooled to room temperature. After step-wise heating and curing, a solid composite is obtained.

[0120] (5) The solid composite was placed in a rotary kiln for carbonization treatment. The temperature was raised to 600° C. at a rate of 3° C. / min in a nitrogen atmosphere with a gas flow rate of 2 L / min, and the temperature was kept at that temperature for 3 hours. The temperature was naturally cooled to room temperature, and the solid composite was ground and sieved (200 mesh) to obtain a carbonized composite.

[0121] (6) The gas introduced into the rotary kiln is switched to carbon dioxide gas to exclude nitrogen gas. The gas flow rate of carbon dioxide gas is 4 L / min. The temperature of the rotary kiln is increased to 1050°C at a rate of 3°C / min to activate the carbonized composite in a carbon dioxide atmosphere. Subsequently, the gas introduced into the rotary kiln is switched to nitrogen gas, and the mixture is naturally cooled in a nitrogen gas environment to finally obtain a silicon-carbon composite material.

[0122] The silicon-carbon composite material prepared in this embodiment was used to prepare the negative electrode plate and assembled into a CR2032 button battery for testing. The specific process was the same as that in Example 1. The test data is detailed in Table 1.

[0123] In order to better illustrate the effects of the embodiments of the present invention, comparative example 1 is compared with embodiments 1-5.

[0124] Comparative Example 1

[0125] This comparative example provides a preparation process and performance test of a traditional silicon-carbon negative electrode material, including the following steps:

[0126] (1) Silicon particles, carbon source precursor polyvinyl pyrrolidone, phenolic resin and antioxidant citric acid were added to an ethanol solution in a mass ratio of 1:1:1:0.1, and sand milled to obtain a dispersion.

[0127] (2) The dispersion is spray-dried to obtain a precursor material.

[0128] (3) vapor-coating the precursor material. Specifically, 1 kg of the precursor material is placed in a rotary furnace, heated to 850° C. under a protective atmosphere, and argon and acetylene gas are introduced at a volume ratio of 2:1 for vapor-coating. The temperature is kept for 1.5 hours, and the organic gas source is turned off. After cooling to room temperature, the material is discharged and classified to obtain a silicon-carbon negative electrode material.

[0129] The conventional silicon-carbon negative electrode material prepared in this comparative example was used to prepare an electrode and assemble a button cell for testing, and the specific process was the same as that in Example 1. The test data is shown in Table 1.

[0130] Table 1 is a summary of the button cell test data assembled in Examples 1-5 and Comparative Example 1:

[0131]

[0132] Table 1

[0133] It can be seen from the test data in Table 1 that the capacity retention rate of the batteries assembled in Examples 1-5 after 300 cycles is greater than that of Comparative Example 1, and the pole piece expansion rate of Examples 1-5 is less than that of Comparative Example 1, indicating that the performance of the battery containing the silicon-carbon composite material of the present invention is better. This is because the silicon dioxide matrix of the silicon-carbon composite material of the present invention has a pore structure, silicon particles are distributed in the pores, and the outer surface of the silicon dioxide matrix has a silicon layer and a carbon coating layer. On the one hand, the silicon particles can increase the specific capacity of the silicon-carbon composite material, and on the other hand, the pore structure in the silicon dioxide matrix can inhibit the volume expansion of the silicon particles, the carbon particles can improve the conductivity of the material, and the carbon coating can inhibit the occurrence of side reactions of the silicon-carbon material. The silicon-carbon composite material is used as a negative electrode active material in a lithium ion battery to improve the electrochemical performance of the lithium ion battery.

[0134] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: The preparation method comprises: Step S1, placing the carbon source material, polyvinyl pyrrolidone and alcohol in a stirring tank and mixing them evenly to obtain a first mixed solution; Step S2, placing the first mixed solution in a sand mill, adding the silica aerogel, and performing sand milling to make the carbon source material evenly distributed in the pores of the silica aerogel, thereby obtaining a second mixed solution; Step S3, drying the second mixed solution to obtain a silicon-carbon precursor; Step S4, uniformly dispersing the silicon-carbon precursor in a box pot, placing the box pot in a box furnace, and performing stepwise temperature rise curing to obtain a solid composite; Step S5, placing the solid composite in a rotary kiln, performing carbonization treatment under an inert gas environment, grinding, crushing and screening to obtain a carbonized composite; Step S6, switching the gas introduced into the rotary kiln to carbon dioxide gas to exclude inert gas, activating the carbonized composite in a carbon dioxide atmosphere, and then switching the gas introduced into the rotary kiln to inert gas, and naturally cooling in an inert gas environment to obtain a silicon-carbon composite material.

2. The preparation method according to claim 1, characterized in that: The carbon source material is a thermosetting alcohol-soluble resin, specifically including: one or more of phenolic resin, epoxy resin, melamine resin, and acrylic resin; The particle size Dv50 of the silica aerogel is 1 μm-5 mm; the pore size of the silica aerogel is 1 nm-100 nm, and the porosity is 80%-90%. The concentration of the alcohol is greater than or equal to 99%; The mass ratio of the carbon source material, polyvinyl pyrrolidone and alcohol is [1-6]: [1-3]: [10-30]; The mass ratio of the carbon source material to the silica aerogel is [100-1000]:[1-5].

3. The preparation method according to claim 1, characterized in that: The rotating speed of the sand mill is 1200 rpm-4000 rpm, and the sand milling time is 1 hour-3 hours.

4. The preparation method according to claim 1, characterized in that: The drying method includes closed spray drying, and the equipment used is a closed cycle spray dryer; the specific conditions of the closed spray drying are: setting the air inlet temperature to 150°C-200°C, the air outlet temperature to 80°C-150°C, and the frequency of the atomizer to 220Hz-280Hz; The mesh size of the solid composite after grinding, pulverizing and screening is in the range of 80 meshes to 300 meshes.

5. The preparation method according to claim 1, characterized in that: The program setting of the step-by-step temperature curing is specifically as follows: heating to 70°C-100°C at a heating rate of 1°C / min-5°C / min, keeping warm for 10 hours-24 hours, then heating to 150°C-250°C at a heating rate of 1°C / min-3°C / min, keeping warm for 6 hours-12 hours, and then naturally cooling to room temperature.

6. The preparation method according to claim 1, characterized in that: The inert gas includes nitrogen and / or argon; the flow rate of the inert gas is 0.5L / min-3L / min; The carbonization treatment program is specifically set as follows: heating to 400°C-700°C at a heating rate of 3°C / min-5°C / min, keeping the temperature for 2 hours-8 hours, and naturally cooling to room temperature; The specific process of causing the carbonized composite to undergo an activation reaction under a carbon dioxide atmosphere is as follows: switching the inert gas to carbon dioxide gas, using carbon dioxide gas as the activation atmosphere, with a carbon dioxide gas flow rate ranging from 2L / min to 8L / min, then heating to 800°C to 1400°C at a heating rate of 1°C / min to 3°C / min, keeping the temperature for 6 hours to 18 hours, then switching the carbon dioxide gas to an inert gas, and naturally cooling to room temperature.

7. A silicon-carbon composite material prepared by the preparation method according to any one of claims 1 to 6, characterized in that: The silicon-carbon composite material comprises: a silicon dioxide matrix containing pores, silicon particles and carbon particles distributed in the pores of the silicon dioxide matrix, and a silicon layer and a carbon coating layer sequentially coated on the outer surface of the silicon dioxide matrix; The silicon-carbon composite material is obtained by loading carbon source materials in the pores and on the outer surface of the silicon dioxide aerogel and sequentially undergoing step-by-step temperature curing, carbonization treatment, and activation reaction.

8. The silicon-carbon composite material according to claim 7, characterized in that: The average particle size of the silicon dioxide matrix is ​​between 1 μm and 10 μm; the pore size of the silicon dioxide matrix is ​​between 1 nm and 100 nm; the average particle size of the silicon particles is between 1 nm and 100 nm; The mass of the carbon coating layer accounts for 0.5%-10% of the total mass of the silicon-carbon composite material; The mass of the silicon particles accounts for 5% to 35% of the total mass of the silicon-carbon composite material; The thickness of the silicon layer is 1 nm-7 μm; the thickness of the carbon coating layer is 10 nm-30 μm.

9. A negative electrode plate, characterized in that: The negative electrode plate comprises the silicon-carbon composite material described in any one of claims 7-8.

10. A lithium ion battery, characterized in that: The lithium-ion battery comprises the negative electrode sheet as claimed in claim 9 above.